Penerapan Metode Tripel Exponential Smoothing Dalam Peramalan Keuntungan Perusahaan dalam Tingkat Penjualan Alat Tulis Kantor - Pulungan, Khairunnisa; Pristiwanto, Pristiwanto (Forum Kerjasama Pendidikan Tinggi, 2021)
Deepening is a step called to determine the profit and loss of a company in its activities. This deepening is related to ATK product and product problems that often occur in a company. CV.Sumber Rezeki has objects that are marketed through marketing and sales counters. The object being marketed consists of three parts namely pens, printer ink, quarto paper and so forth. The problem of determining the cost of sales in CV. Source of sustenance is often faced by a company. The contributing factor is the amount of goods produced is not in accordance with the needs of consumers, so there is a buildup of stock of goods that can result in losses on the source of sustenance. Determination of sales costs can be completed using the triple exponential smoothing method. Several ways to solve problems with triple exponential smoothing. Among them are resolved using the smoothing method. Triple exponential smoothing method. is one of the settlement techniques in triple exponential smoothing. which is used as a decision-making technique in matters relating to the optimal allocation of resources.